Growth and characteristic of high orientation indium nitride films grown on (100) silicon substrate. (1st January 2014) - Chen, Wei-Chun; Chen, Hung-Pin; Kuo, Shou-Yi; Lin, Woei-Tyng; Lai, Fang-I; Hsiao, Chien-Nan; Lee, Cheng-Chung
In this study, high orientation InN films were prepared on Si (100) substrates using plasma-assist metal-organic molecular beam epitaxy (RF-MOMBE) system. These buffers include the nitrided treatment of the Si substrate, a low-temperature AlN buffer layer and oxide layer. The crystalline structure, surface morphology and optical properties of the InN films were characterised by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscope (SEM), atomic force microscopy (AFM) and photoluminescence (PL) measurements. XRD results revealed that the wurtzite InN grows on oxide layer with preferential (0002) orientation. Bright-field XTEM images of InN films exhibit a hexagonal structure with highly preferred orientation along <0001≯ direction. InN film direct growth on Si substrate exhibited the formation of metallic indium droplets on the surface. AFM images revealed that InN films with oxide layer had a root-mean-square (RMS) roughness of 16.1 nm. The optical properties of InN/oxide layer were determined according to the photoluminescence, revealing a near band-edge of 0.719 eV.